A comparative study of turbulence models for predicting the aerodynamic drag of a spin-stabilized projectile - Nguyen, Quang Tuan (Vojnotehnički glasnik / Military Technical Courier, 2025)
Introduction/purpose: In this research, the influence of different turbulence models on the aerodynamic drag prediction of a generic spin-stabilized projectile was analyzed. The turbulence models chosen for investigation were one-equation Spalart-Allmaras, two-equation models Standard k-ε, Realizable k-ε, Standard k-ω and SST k-ω. The special sniper projectile M118 was selected for the study. Methods: The flows around the projectile were numerically simulated using RANS equations intergrated into ANSYS Fluent software with different turbulence models. The numerical simulation was carried out at various Mach numbers to study the effect of turbulence models on the projectile aerodynamic drag prediction. The computational results were compared to the available experimental data to evaluate the ability of the turbulence models . Results: The research results have shown that the turbulence models significantly affect the numerical simulation results. The Spalart-Allmaras turbulence model performs better than other models in the subsonic flow regime. The Standard k-ε, Realizable k-ε and SST k-ω models perform better than other models in the supersonic flow regime. Conclusion: Computational Fluid Dynamics is a powerful tool to analyze the aerodynamics of flying bodies. By appropriately selecting turbulence models, the flow around flying bodies can be accurately investigated. In the case of generic ogive-cylinder-boattail projectiles, on the one hand, the Spalart-Allmaras model is suitable for subsonic flow, and the Standard k-ε, Realizable k-ε and SST k-ω models are recommended for the supersonic flight regime, on the other hand.